The inviolability of embassies and consulates: regarding the dispute between Mexico and Ecuador before ICJ - Collantes Gonz´ález, Jorge Luis (2024)
On April 5, 2024, Ecuadorian security forces entered the Mexican Embassy in Quito without authorization to apprehend the former Vice President of Ecuador, Jorge Glas, who had been granted asylum within the embassy. This incident prompted both Mexico and Ecuador to present the case before the International Court of Justice (ICJ), thereby underscoring the significance of the 1961 Vienna Convention on Diplomatic Relations (VCDR). The ICJ has emphasized the inviolability of embassies and diplomats as a fundamental principle to be upheld by the international community. Consequently, the Mexico-Ecuador case raises critical questions regarding physical inviolability, the misuse of technology, and the granting of asylum to evade criminal liability. This situation highlights the necessity of respecting the inviolability of diplomatic missions and pursuing peaceful and legal resolutions in international conflicts, reaffirming the importance of the principles enshrined in the VCDR and international public law.